Air pollution and corporate labor cost stickiness: Evidence from China - Jiao Ma (PLoS ONE, 2025)
Air pollution is a common environmental issue worldwide, and its impact on macroeconomic development has always been of great concern. The role of air pollution on corporate behavior is a relatively new micro-perspective. By matching city-level air pollution data with data from A-share firms in China, the relationship between air pollution and corporate labor cost stickiness was examined. The study found that air pollution significantly increased corporate labor cost stickiness, especially for rank-and-file employees, with no significant impact on the labor cost stickiness of managers. Corporate good ESG performance can weaken the positive correlation between air pollution and labor cost stickiness. Air pollution exacerbates corporate labor cost stickiness through the mechanisms of salary compensation and the flow of labor forces. This positive correlation is more pronounced in firms located in areas with weaker traditional cultural influence, lower government focus on talent and lower environmental regulation stringency. This study enriches the research on the impact of air pollution on corporate governance, providing new evidence and ideas for the interdependence of environmental and economic benefits.